PENGARUH LIMBAH BAMBU SEBAGAI MEDIA TUMBUH PADA KANDUNGAN PROKSIMAT JAMUR TIRAM (Pleurotus ostreatus) DI PT. BUKIT ASAM-TBK PELABUHAN TARAHAN - Ali, Fahri; Prajaka, Nanang Wahyu; Sesanti, Rizka Novi; Maulana, Erie; Mabruroh, Fifki Nugraeni; Hamdani, Hamdani (Agros Journal of Agriculture Science, 2024)
The oyster mushrooms are generally cultivated on baglog medium, which is produced from leftover wood sawdust. The oyster mushroom may thrive in a variety of cellulose, hemicellulose, and lignin-containing substrates medium. The purpose of this study was to determine the effect of leftover bamboo powder waste on the proximate content of oyster mushrooms when it was utilized as a growing medium in mushroom baglogs. This study was carried out at the Lampung State Polytechnic of Mushrooms Kubung from August to October 2022. The test material consisted of oyster mushrooms collected from mushroom baglogs constructed of 100% sawdust, 100% coarse bamboo waste, 100% fine bamboo waste, and 50% coarse bamboo waste + 50% fine bamboo waste. Three harvests of oyster mushrooms were made on various media types for testing purposes in the lab. According to this study's findings, oyster mushrooms grown on bamboo powder media have a better value than oyster mushrooms grown on wood sawdust media in terms of their proximate content of water, protein, fat, and carbohydrates. Key-words: Bamboo Powder, Nutrition, Oyster Mushroom, Proximate, Wood Sawdust INTISARI Jamur tiram umum ditumbuhkan pada media baglog yang berbahan dasar limbah serbuk gergaji kayu. Jamur tiram memiliki kemampuan untuk tumbuh di berbagai jenis media yang mengandung selulosa, hemiselulosa, dan lignin. Tujuan penelitian ini untuk mengetahui pengaruh dari limbah serbuk bambu yang digunakan sebagai media tumbuh dalam baglog jamur pada kandungan proksimat jamur tiram. Penelitian ini dilaksanakan pada bulan Agustus – Oktober 2022 di Kubung Jamur Politeknik Negeri Lampung. Bahan uji yang digunakan adalah jamur tiram yang dipanen dari baglog jamur berbahan dasar utama Limbah bambu kasar 100%; Limbah bambu halus 100%, Limbah serbuk kayu 100%; dan Limbah bambu kasar 50%+Limbah bambu halus 50%. Jamur tiram yang dipanen pada setiap jenis media dilakukan tiga kali pengulangan untuk keperluan pengujian di dalam laboratorium. Kesimpulan dari penelitian ini adalah kandungan proksimat kadar air, protein, lemak dan karbohidrat jamur tiram yang ditumbuhkan pada media serbuk bambu memiliki nilai lebih tinggi dibandingkan dengan jamur tiram yang ditumbuhkan pada media serbuk gergaji kayu. Kata kunci: Gizi, Jamur tiram, Proksimat, Serbuk bambu, Serbuk gergaji kayu